Evaluating a School-Based Anti-Bullying Intervention: A Case Study from North Sumatra - Yana, Suci Pitri; Nurhanifah, Nurhanifah; Ramadhan, Rasyiidha Witra; Lubis, Mhd Rasyid Syaf (PPSDP International Journal of Education, 2025)
Bullying remains a significant concern in educational settings, negatively affecting students’ academic performance, motivation, mental health, and social relationships. This study aimed to examine students’ understanding of bullying including its definition, forms, impacts, and preventive strategies and to evaluate the effectiveness of an educational intervention in promoting a supportive learning environment. The intervention was conducted with students of Junior High School Swasta Karyawan Turangi by real work lecture students from State Islamic University of North Sumatra in 2025. The program involved a structured presentation, interactive discussions, and a comprehension assessment through an ice-breaking ball-toss activity combined with singing. Results indicated that some students had experienced bullying, particularly in the form of physical ridicule or verbal insults, while others reported no such experiences. The intervention successfully enhanced students’ knowledge about bullying and fostered collective awareness regarding the importance of maintaining a safe, bullying-free learning environment. These findings underscore the need for systematic educational programs to prevent bullying in schools.